The discursive construction of the moral and legal statuses of fansubbers in the Chinese press 2006–2018. (June 2020) - Wu, Zhiwei
Highlights: A diachronic corpus of media representations of Chinese fansubbers was built. Media frames, discourse topics, and discursive strategies were examined. The discourse topics of sharing and volunteerism feed into a moral frame. The discourse topics of copyright and commercialization feed into a legal frame. Transitivity patterns and nomination strategies are dynamic and complex. Abstract: Fansubbers (short for "fan subtitlers") are confronted with a moral-legal dilemma in China. On the one hand, they are highly appreciated by the general public because they work without pay and altruistically provide free access to subtitled audiovisual contents that are otherwise unavailable. On the other hand, they distribute unlicensed contents and violate the copyright law in China. Their practices cause damages to copyright holders and thus call for legal actions. Given the conflicting moral and legal statuses, it is necessary to understand how the Chinese press frame and represent fansubbers, as the media play a crucial role in shaping people's opinions. Drawing on a one-million-word corpus of news reports between 2006 and 2018, this study examines the media frames, discourse topics, and representations about fansubbers in China. Based on keyword, collocation, and concordance analyses, four discourse topics were identified: sharing, volunteerism, copyright, and commercialization . The former two pointed to a moral frame, while the latter two fed into a legal frame. The diachronic analysis demonstrated that the topic of sharing was most prominent in eight of 13 years, while the topic of copyright spiked about every five years. The corpus findings also unravel the complexities of discursive strategies in two aspects: (a) representational strategies work in combination to selectively frame fansubbers and (b) the same discursive strategies can simultaneously moralize and delegitimize fansubbers. This study sheds light on the multifaceted, dynamic, and complex nature of media representations about fansubbers with a conflicting social position.